Food, microbiome and colorectal cancer. Issue 7 (July 2018) - Niederreiter, Lukas; Adolph, Timon E.; Tilg, Herbert
Abstract: You are what you eat. This adage has been confirmed by many studies demonstrating the high impact of nutrition on risk of cardiovascular diseases, many malignancies and other diseases. Dietary factors are of major relevance in the evolution of colorectal carcinoma. Various aspects are involved in colorectal carcinoma pathogenesis including genetics, lifestyle, age, chronic inflammation and others. It has only recently been recognized that the gut microbiota might reflect an important missing link in the interaction between diet and subsequent colorectal carcinoma development. Dietary factors are a major confounding factor affecting the composition of the intestinal microbiota. Several preclinical and clinical studies have recently suggested a role for the intestinal microbiota in potentially initiating and driving colorectal carcinoma. Therefore it is increasingly acknowledged that dietary factors might favor carcinogenesis via manipulation of the gut microbiota via potential outgrowth of certain bacterial populations, such as Fusobacterium nucleatum, Escherichia coli or Bacteroides fragilis . Excitingly, recent large clinical studies also highlighted a role for the gut microbiota and in particular Akkermansia muciniphila in tumor response toward chemotherapeutic agents and immune checkpoint inhibitors. This review will concentrate on the role of dietary factors in affecting the microbiota and implications in colorectal carcinoma.